2022
DOI: 10.1039/d2qi01544g
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive SAPO-seeded synthesis of ZK-5 zeolite for selective synthesis of methylamines

Abstract: The selectivity for monomethylamine plus dimethylamine is urged to be improved in selective synthesis of methylamines due to their high value as the chemical intermediates. ZK-5, a small-pore zeolite, shows...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Zeolite materials have emerged as promising candidates for this purpose owing to their molecular sieving capability and adjustable acid properties. For instance, large-pore MOR zeolite with a 12-membered-ring window of 6.5 Å × 7.0 Å was commercially utilized in methylamines (MAs) production during the 1980s [7] . However, a pore-size-reduction post-treatment was necessary to enhance the yield of MMA plus DMA.…”
Section: Introductionmentioning
confidence: 99%
“…Zeolite materials have emerged as promising candidates for this purpose owing to their molecular sieving capability and adjustable acid properties. For instance, large-pore MOR zeolite with a 12-membered-ring window of 6.5 Å × 7.0 Å was commercially utilized in methylamines (MAs) production during the 1980s [7] . However, a pore-size-reduction post-treatment was necessary to enhance the yield of MMA plus DMA.…”
Section: Introductionmentioning
confidence: 99%
“…39,40 However, there have only been a few studies involving heteronuclear seeds due to insufficient recognition of the related principle. 17,[41][42][43] A recent result of the seed-assisted synthesis of zeolite Y revealed that only partial dissolution with solid residue is crucial for a qualified seed, where hydrogel microparticles migrate and attach, inducing fast nucleation and crystal growth. 44 But the working mechanism of a seed in a SAPO system has been rarely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Consequently, the large TMA distribution in the products greatly limits the overall efficiency for DMA production. Although advanced silica-alumina catalysts were reported to suppress TMA formation via methanol animation to some extent, [11][12][13] the development of a cost-effective and less energyintensive method to directly channel TMA into DMF production is desirable to enhance the synthetic efficiency of DMA.…”
Section: Introductionmentioning
confidence: 99%